Penerapan Model Pembelajaran Kooperatif TGT (Teams Game Turnamens) untuk Meningkatkan Motivasi dan Prestasi Belajar Siswa MAN 2 Pesisir Selatan - Nurhayati Nurhayati (Departement of Mathematics Education, 2023)
This study aims to determine the increase in learning motivation and student learning outcomes of MAN 2 Pesisir Selatan applying the TGT (Teams Game Tournament) cooperative learning model. The approach used in the research here is a qualitative approach and the type of research is Classroom Action Research (PTK). PTK is an examination of learning activities in the form of an action, which is deliberately raised and occurs in a class together (Arikunto, 2006:3). The research will be carried out in 2 cycles, each consisting of 4 stages. The research design used consisted of 4 components, namely planning, action, observation and reflection. The research subjects were students of class XI IA3 at MAN 2 Pesisir Selatan in the odd semester of 2018/2019, a total of 36 students. The results of the study show that first, the application of the TGT (Teams Game Tournaments) cooperative learning model can increase student motivation in MAN 2 Pesisir Selatan. Second, the application of the TGT (Teams Game Tournaments) cooperative learning model can improve student achievement at MAN 2 Pesisir Selatan.